Influence Of Ion Implantation And Bombing On Solid Substances Surface And Areas Close To The Surface - et. al., R.U. Elmurodov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, under vacuum conditions, ions of substances are implanted or bombarded with these ions in the surface and areas close to the surface, as well as by growing films or coatings from other metallic materials on the surface of these bases by simultaneous thermal evaporation. or the interaction of atoms of coating materials and the formation of multi-component solid alloys, which can be studied in several ways.